1997
DOI: 10.1136/thx.52.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nurse-led home management training programme in children admitted to hospital with acute asthma: a randomised controlled study

Abstract: Abstracthood asthma. 1 2 Asthma re-admissions are also Background -Re-admissions to hospital common. For example, Senthilsevan recently in childhood asthma are common with reported that re-admission rates (asthma restudies reporting that 25% or more of chil-admissions/all asthma admissions) for children dren will be re-admitted within a year. from all 134 hospitals in Saskatchewan ProvThere is a need for strategies to reduce re-ince, Canada were between 20% and 30% admissions.during the decade 1980-9. 3 Mitche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 20 publications
4
139
2
3
Order By: Relevance
“…Education and discharge planning are extremely important in the management of childhood asthma. Improving children's and parents' awareness and understanding of asthma, contributes to a positive outcome [19,20]. The proportion documented as receiving education in this study was low, as has been found in other recent studies [21].…”
Section: Discussionsupporting
confidence: 70%
“…Education and discharge planning are extremely important in the management of childhood asthma. Improving children's and parents' awareness and understanding of asthma, contributes to a positive outcome [19,20]. The proportion documented as receiving education in this study was low, as has been found in other recent studies [21].…”
Section: Discussionsupporting
confidence: 70%
“…[11][12][13] This low-cost, high-volume intervention was easily integrated into routine discharge planning for patients at the hospital. Although similar to the smaller programs in intensity, approach, content, and objectives, it differed in its selection of patients and staffing.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Three other studies, each reaching fewer than 100 children, focused primarily on patient/caregiver education and support in the hospital during the child's stay. [11][12][13] These latter studies demonstrated a reduction in repeat ED visits and hospitalizations among participants.…”
Section: Introductionmentioning
confidence: 88%
“…Most programs target children's self-management, which is not an appropriate intervention for preliterate children [13][14][15]19,22,24,33,35,68,85]. None of the programs focused on young children's self-regulation of thoughts, feelings, and behaviors.…”
Section: Literature Gaps: Recommendations Future Researchmentioning
confidence: 99%
“…Following diagnosis, children with asthma must learn effective medical self-management [13]. Since studies have suggested that selfmanagement of asthma is essential to minimizing asthma exacerbations, teaching behavioral elements (avoiding triggers) and the proper use of tools (inhalers and peak flow meters) could have a substantial effect on children's asthma morbidity [1,33,34].…”
Section: Content: Self-regulationmentioning
confidence: 99%